Conduction block in neuropathies with necrotizing vasculitis - Ropert, A; Metral, S (Muscle & nerve, 1990)
Thirty-two patients with a mononeuropathy multiplex associated with a systemic necrotizing vasculitis were studied. The main abnormality was a loss of motor and sensory axons confirmed by electrophysiological and histological methods. A conduction block was observed in five patients, but only one was at a usual site of compression. Based on previous pathological studies and the experimental data in human and animals, the mechanism of the block is proposed to be ischemic. It is suggested that a conduction block in one nerve in a neuropathy with two or more individual nerves affected and with electrophysiological features of axonal degeneration may be due to a vasculitis.